The Adaptation of Participation Scale Short Simplified Questionnaire into Indonesian Language and the Psychometric Properties in Individuals with Type 2 Diabetes Mellitus with Vestibular Dysfunction. (15th June 2022) - Komalasari, Dwi Rosella; Vongsirinavarat, Mantana; Hiengkaew, Vimonwan; Nualnim, Nantinee
Abstract : Background . Type 2 diabetes mellitus (T2DM) has been reported to affect the vestibular system resulting in dizziness and vertigo complaints. This complication is known to disable the social participation. The Participation Scale Short Simplified (PSSS) has been developed to quantify the severity of social participation restrictions. The aim of this study was to translate and cross-culturally adapt the PSSS into Indonesian Bahasa (PSSS-Ina). The measurement properties of the translated version and the factors contributing to the severe participation restriction were determined. Methods . The participants comprised 55 T2DM with vestibular dysfunction (VD) in the community center for diabetes mellitus in Central Java, Indonesia. The signs of VD were confirmed by head impulse test, Dix Hallpike Test, and supine roll test. The PSSS-Ina was administered twice with a four-week interval. The physical examination was also performed to identify the contributing factors. Results . The test–retest reliability of the PSSS Indonesian Bahasa version (PSSS-Ina) between two measurement sessions was excellent (ICC of 0.93, p < 0.001, and 95% CI: 0.88–0.95). The correlation coefficient between two administrations was high (r = 0.88 ). Based on the demonstrated content validity, the values of the corrected item and total correlation were greater than 0.3. No floor and ceiling effects were observed. The good internal consistency was confirmed with Cronbach's alpha of 0.84. The factor analysis produced three factors of activity participation, social engagement, and work-related participation. The multiple logistic regression revealed that the balance performance of mCTSIB was the main factor contributing to the severe participation restriction reflected by the PSSS-Ina score. Conclusion . The Indonesian version of the PSSS-Ina demonstrated excellent comprehensibility and reliability in individuals suffering T2DM with VD. This tool is therefore helpful in identifying the participation limitation in individuals with VD.